Numerical simulation of the stress-strain state of complex-reinforced elements - Krantovska, Olena (Array, 2019)
The article describes a developed technique of a numerical simulation of the stress-strain state of complex-reinforced elements, which allows you to create models of double-span continuous. The performed experimental and theoretical studies allowed us to carry out the testing of the developed design model and to justify the reliability of the proposed numerical simulation methodology. The results of the experimental studies were compared with those of the theoretical studies. The theoretical calculus algorithm was developed by using the finite element method. Theoretical calculations were performed by using the mathematical-graphical environment software system LIRA-SOFT and the mathematical and computer program MATLAB. On the basis of the experimental research, the iso-fields of displacements and stresses in the materials of an eccentrically compressed beam with a small bend of the slab were constructed, which collapse behind the inclined narrow strip of concrete and displacements and stresses in the materials of the eccentrically stretched beam, which is destroyed due to the yield of the upper mounting armature.